2019
DOI: 10.1007/978-3-030-22012-9_16
|View full text |Cite
|
Sign up to set email alerts
|

Improved Knowledge Changes the Mindset: Older Adults’ Perceptions of Care Robots

Abstract: This paper explores Finnish, German and Swedish older adults' perceptions of a future welfare service with increased use of welfare technologies, specifically care robots. The issues are the rapid digitalization and development of health and welfare technology, which presently is mainly technology driven (not need or user driven), and the demographic challenge. The aim of the study was to explore older adults' perception of the future use of welfare technology or care robots. A qualitative approach with focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Additionally, differences in the attitudes of students from different countries and regions (eg, Japan vs Europe) are worth exploring [ 45 ]. Moreover, the inclusion of potential end users from older generations as well as other stakeholders (family members, professional caregivers, etc) might yield noteworthy results, as indicated in a range of previous studies [ 20 , 28 , 31 , 33 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, differences in the attitudes of students from different countries and regions (eg, Japan vs Europe) are worth exploring [ 45 ]. Moreover, the inclusion of potential end users from older generations as well as other stakeholders (family members, professional caregivers, etc) might yield noteworthy results, as indicated in a range of previous studies [ 20 , 28 , 31 , 33 ].…”
Section: Discussionmentioning
confidence: 94%
“…This corresponds with the observation of Flandorfer that the more experienced people are in using new technologies and the smarter the devices, the higher is the desire to use such devices when needed [ 18 ]. Johansson-Pajala et al also observed that the attitudes of study participants to care robots improved as their knowledge increased [ 33 ], which was interpreted as a general need for an improved orientation within the field.…”
Section: Discussionmentioning
confidence: 99%
“…Johansson-Pajala et al . (2019) concluded that a successful implementation of health and welfare technology heavily depends on receiving relevant information, meeting older people's authentic needs and considering the hesitance of professional caregivers. In the results of the current study, only 12 of the 17 health professionals in primary and home health care, assistant nurses in home care and care managers considered having access to individualised health and welfare technology for increased surveillance in the home to be a prerequisite for a healthy and independent life (#33), while all 12 older persons and all five politicians did.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual interviews resulted in some Wi-Fi technical issues and the inability to see the telepresence robot in person. They were shown a mirror of how they were controlling the robot from their end, however, the experience may have been different if they had seen the technology in person, as it would have given them the element of design and expanded the concept of usage, as attitudes improved with more knowledge of the robot (Johansson-Pajala et al, 2019). Purposive sampling enabled diversity in the participants in terms of interdisciplinary studies, ethnicity, gender, and age allowing for diverse perspectives.…”
Section: Strengths and Limitationsmentioning
confidence: 99%